The effects of dredging and environmental conditions on concentrations of polycyclic aromatic hydrocarbons in the water column. (October 2018) - Vagge, Greta; Cutroneo, Laura; Castellano, Michela; Canepa, Giuseppe; Bertolotto, Rosa Maria; Capello, Marco
Abstract: Sediment dredging can cause damage to the marine environment due to mobilization of sediments and contaminants. The effects of dredging and boundary environmental conditions on the concentration of Polycyclic Aromatic Hydrocarbons (PAHs) in water were evaluated during dredging of the Oil Port of Genoa-Multedo (Italy). Results showed that turbidity and PAH concentrations increased in the water during dredging. However, the scenario was complex due to the high number of interacting physical-chemical factors influencing PAH concentrations and transport. Due to these, PAH distribution is different in water, where low-molecular-weight PAHs were predominant (maximum concentration 0.105 μg L −1 ), and in bottom sediments, where high-molecular-weight PAHs had the highest concentrations (from 299.3 to 1256.5 ng g −1 ). Moreover, mainly during dredging the PAH concentrations in water were significantly higher inside than outside the port as a consequence of the lower dynamics within the port basin. Turbidity was the main parameter related to PAH concentrations. Graphical abstract: Highlights: Dredging and boundary condition effects on PAH concentrations in the water column Predominance of Low Molecular over High Molecular Weight PAHs in the water column Predominance of High Molecular Weight PAHs remains in the sediments during dredging.